Multi‐element characterisation of carob, fig and almond liqueurs by MP‐AES. Issue 3 (22nd May 2018) - Rodríguez‐Solana, Raquel; Carlier, Jorge Dias; Costa, Maria Clara; Romano, Anabela
Abstract : Carob pod, fig and almond liqueurs are produced in various Mediterranean regions. This work reports the mineral content of these traditional beverages and evaluates the influence of the raw material. Twenty‐five fruit liqueurs from 16 producers were analysed. A simple open‐vessel sample mineralization by wet digestion using nitric acid–hydrogen peroxide (1:1) was used before spectrometric analysis. Nine essential elements (Cu, Ca, Mg, Na, K, Fe, Zn, Mn and P) and two non‐essentials (Cd and Pb) were quantified by microwave plasma–atomic emission spectrometry (MP‐AES). Carob liqueur presented the broader profile of minerals and was the only fruit liqueur containing iron (72.7% of samples), phosphorous, manganese and low levels of lead (in two of the 11 samples). Conversely, almond liqueurs contained the lowest mineral content with only five elements detected. Fruit liqueurs showed variability in mineral content even within the same liqueur, presumably as a consequence of the different manufacturing processes. Despite this variability, application of principal component analysis to essential mineral concentrations (K, Na, Ca, Mg, Mn, Fe and Zn) resulted in satisfactory classification (PC1 and PC2 accounting for 78.5% of the total variance) of the Portuguese liqueurs evaluated. Copyright © 2018 The Institute of Brewing & Distilling